Are there ‘hygiene-motivation’ factors in the choice of India as a tourist destination? A structural equation modelling approach - Vlad Diaconescu (Cactus)
This study examines the role of motivational factors in the selection of India as a travel destination, using Herzberg’s two-factor theory of motivation (Hygiene-Motivation model) as a theoretical foundation. By examining how stereotypes about India influence tourists' decision making, this study categorises motivational factors into hygiene and motivation categories and examines their influence on destination choice. A survey conducted at the Romanian Tourism Fair in February 2019 with 729 participants forms the basis for this analysis. Structural equation modelling (SEM) was applied to assess the relationships between these factors. The study reveals two main types of factors that influence tourists: Hygiene factors (e.g. accessibility, comfort, food and overall quality of services) and motivational factors (e.g. cultural richness, scenic beauty and local traditions). The study shows that stereotypes about India play a crucial role in shaping tourists’ priorities — those who have negative stereotypes are more likely to focus on hygiene factors, such as ensuring that basic service expectations are met. In addition, while motivational factors still play an important role, elements such as natural beauty and cultural experiences take centre stage in the travel decision.